1987
DOI: 10.1177/0893318987001002003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Interpreting Organizational Culture

Abstract: This article offers a triangulation approach to the study of organizational culture by employing reliably coded interviews to help interpret and place in context the results of statistical analyses from a standardized survey questionnaire. Subjects were 195 government employees representing every level and division in their department. All 195 subjects completed the Organizational Culture Survey and 91 subjects participated in 45-minute critical incident interviews designed to elicit subjects' interpretations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 18 publications
3
156
0
5
Order By: Relevance
“…The quality of co-worker relationships reflects levels of work behaviors such as helping, communication, and coordination among employees engaged in inter-dependent tasks [31]. This notion of co-worker relationship quality was identified with "teamwork/conflict" in a study by Glaser et al [32] (p. 194). According to this study, teamwork can be defined as "reported coordination of effort, interpersonal cooperation, rapport, or antagonism, resentment, jealousy, mistrust, power struggle between sections or divisions; (and the extent to which) people talk directly and candidly about problems they have with each other".…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of co-worker relationships reflects levels of work behaviors such as helping, communication, and coordination among employees engaged in inter-dependent tasks [31]. This notion of co-worker relationship quality was identified with "teamwork/conflict" in a study by Glaser et al [32] (p. 194). According to this study, teamwork can be defined as "reported coordination of effort, interpersonal cooperation, rapport, or antagonism, resentment, jealousy, mistrust, power struggle between sections or divisions; (and the extent to which) people talk directly and candidly about problems they have with each other".…”
Section: Hypothesesmentioning
confidence: 99%
“…This variable was measured using a six-item scale developed by Glaser et al [32]. This measure captures group-level coworker communication, cooperation, and helping behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The survey developed based on previous studies (Bass & Avolio, 2004;Glaser, Zamanou, & Hacker, 1987;Herscovitch & Meyer, 2002;Schrodt, 2002). This survey was divided into three sections, the first section was the demographic factors, the second section was on the change profile and the final section was on the key factors, which were: a) employee commitment to change; b) transformational and transactional leadership; c) organisational culture.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Organizational culture has frequently been described by organizational researchers as involving shared meaning, normative patterns, or expectations that evolve over time within organizations (Glaser, Zamanou, & Hacker, 1987;Schein, 2010;Schneider, Ehrhart, & Macey, 2013). Although the foci of these definitions vary, most agree that it is not an easily identifiable or neatly integrated concept; rather, it is an aggregation of complex subordinate concepts (Glaser et al, 1987).…”
Section: Work Environmentmentioning
confidence: 99%